Hobart - Kudelka, Jon (South Hobart, Tasmania, Australia : Kudelka Productions, 2015)
"This book is my love letter to Hobart. With cartoons... It's by no means definitive, just a bunch of notions I scribbled down on a plane, so on the off chance any Northern types (you know who you are) reading this don't get some of the jokes, you'll just have to come and live here to find out. Pack a jumper."--Jon Kudelka, Introduction.
Some cartoons previously published in: Dark Hobart, 2014.
Keywords: Kudelka, Jon; Winter -- Tasmania -- Hobart -- Caricatures and cartoons; Caricatures and cartoons -- Tasmania -- Hobart; Caricatures and cartoons -- Tasmania -- Wellington, Mount; Australian wit and humor, Pictorial -- Tasmania; Cartoonists -- Tasmania; Hobart (Tas.) -- Humor; Hobart (Tas.) -- Social life and customs -- Caricatures and cartoons; Hobart (Tas.) -- Pictorial works; Wellington, Mount (Tas.) -- Caricatures and cartoons; Tasmania -- Pictorial works; Australian